Dates Loss and Its Impact on Food Security and the Environment in the Kingdom of Saudi Arabia - Emam, Abda; Abass, Amal (European Journal of Applied Sciences, 2025)
Worldwide, the numeral of people distresses from hunger or severe food insecurity. This condition is giving attention and considering the massive amount of food discarded globally through Sustainable Development Goals (SDGs). Hence, the study projected to exam dates loss (ton) and its impacts on food security and environment in Saudi, using dates losses, dates production (ton) and CO2 emissions as variables of the study. Annual ‎data was collected for period extended from 2010 to 2023 from FAO statistics and examined by applying ARDL analysis tests and Vector Error Correction Model. The outcomes of the co-integration test revealed that there is a long-run association among dates loss and dates production. Reference to short run relationship, no significant short-run effects from lagged of dates production on dates loss. In addition, the study indicated that dates losses at farm gate lead to reduced food availability along supply chains which resulting in a decrease in the volume of food existing for human consumption leading to affect adversely on food security. Furthermore, the results appeared that there absent of long run relationship between dates losses quantities and CO2 emissions, concluding that dates losses have no effect on environment (CO2 emission). This result may be due to reuse or recycle of dates quantities losses as feed to animal inside the farm. To achieve national food security and sustainable agriculture goals some recommendations were ‎drawn from results: minimize or lessen date losses at the producer level through stablishing reliable nationwide practices for date palm harvesting and post-harvest handling.